Internalization advantage and subsidiary performance: The role of business group affiliation and host country characteristics - Gaur, Ajai S; Pattnaik, Chinmay; Singh, Deeksha; Lee, Jeoung Yul (Journal of International Business Studies, 2019)
We extend internalization theory by examining the contingencies associated with market internalization and its impact on foreign subsidiary survival. Based on a sample of 6170 subsidiary–year observations in 63 countries belonging to 292 MNCs from Korea during 1995–2013, we find that greater product and labor market internalization have weaker impacts on the survival of subsidiaries operating in countries with more developed institutional environments but stronger for subsidiaries of MNCs affiliated with business groups. The impact of business group affiliation is further dependent on host country institutional development, and the diversification and size of the business group.